Implementation of the Public Order Policy by the Civil Service Police Unit in Minahasa Regency - Maindoka, Giovanni; Bulo, Laurens L.; Tarore, Steven V. (International Journal of Information Technology and Education, 2025)
This study aims to examine and analyze the implementation of public order policy by the Civil Service Police Unit (Satpol PP) in Minahasa Regency, as well as to identify the factors that hinder its execution. Public order is a crucial aspect in creating a safe, orderly, and comfortable social environment. However, in practice, Satpol PP in Minahasa Regency faces various structural and functional challenges that affect the effectiveness of the policy implementation. This research employs a qualitative approach with data collection techniques including in-depth interviews, direct observation, and document analysis. Data analysis was conducted using the interactive model proposed by Miles, Huberman, and Saldaña, which involves data condensation, data display, and conclusion drawing/verification. The results of the study indicate that the implementation of public order policy has been carried out through several key activities such as early detection and prevention, community education and outreach, patrols, security, enforcement, and inter-agency coordination. Nevertheless, the implementation remains suboptimal due to several inhibiting factors, including the absence of a specific regional regulation (Perda) on public order, limited human resources and operational facilities, weak coordination among institutions, and low public awareness of existing regulations. The study concludes that the success of policy implementation heavily depends on the clarity of local regulations, budgetary support, and community participation. Strategic efforts are needed from the local government to strengthen the legal and institutional framework to enhance the effectiveness of public order policy enforcement in Minahasa Regency.